Brachytherapy and 3D printing for skin cancer: A review paper - Poltorak, Michal; Banatkiewicz, Pawel; Poltorak, Lukasz; Sobolewski, Piotr; Zimon, Damian; Szwast, Maciej; Walecka, Irena (Journal of Contemporary Brachytherapy, 2024)
Brachytherapy is a type of radiation therapy, in which a radiation source is placed directly or close to a tumor. It is commonly used to treat skin cancer, and enables precise irradiation treatment of affected area (planning target volume – PTV) while minimizing exposure dose to surrounding healthy tissue (organs at risk – OARs). Recently, the use of 3D printing has begun revolutionizing brachytherapy, as it allows manufacturing of custom-designed applicators for unique shape of skin topography, tumor, and surrounding tissues. Outcome of the combination of 3D printing and brachytherapy has several advantages over traditional treatment planning methods. Some of the advantages are intuitive, whereas others can be concluded from a literature overview as follows: 1) Possibility of developing patient-specific applicators that precisely match the shape of tumor area; 2) Reduction of the time required for applicator production, especially when custom-made devices are needed; 3) Reduction of manufacturing costs; 4) Treatment procedures improvement; 5) Improvement of safety measures accelerated by the development of smart materials (e.g., polymer filaments with admixture of heavy elements); 6) Possibility of nearly instant adjustment into tumor treatment (applicators can be changed as the tumor is changing its shape); and 7) Applicators designed to securely fit to treatment area to hold radioactive source always in the same place for each fraction. Consequently, tumor-provided dose is accurate and leads to effective treatment. In this review paper, we investigated the current state-of-the-art of the application of 3D printing in brachytherapy. A number of existing reports were chosen and reviewed in terms of printing technology, materials used, treatment effectiveness, and fabrication protocols. Furthermore, the development of future directions that should be considered by collaborative teams bridging different fields of science, such as medicine, physics, chemistry, and material science were summarized. With the indicated topics, we hope to stimulate the innovative progress of 3D printing technology in brachytherapy.